Biomechanical Comparison of Canine Fascia Lata and Thoracolumbar Fascia: An In Vitro Evaluation of Replacement Tissues for Body Wall Reconstruction. Issue 1 (28th July 2014) - Henderson, Elisabeth R.; Friend, Ed J.; Toscano, Michael J.; Parsons, Kevin J.; Tarlton, John F.
<x xml:space="preserve">Abstract</x> Objectives To compare the suitability of thoracolumbar fascia (TLF) and fascia lata (FL) for body wall defect repair in dogs, by examining their biomechanical properties and useable surface area. Study Design Experimental. Animals Dogs (n = 8). Methods Fresh TLF and FL grafts were obtained, surface area was calculated before testing to failure in 2 different modes: tensile testing and resistance to suture pullout, in 2 perpendicular orientations. Results Useable TLF surface area was significantly greater than for FL. Maximum load, energy to break, and elastic modulus of FL was significantly greater than that of TLF in tensile testing, but no apparent difference in the ultimate stress or strain was identified. There was no overall difference in suture pullout load between TLF and FL. During tensile testing, tissue orientation had a significant influence on ultimate load, stress, and elastic modulus for both tissue types, with strain and energy to break only having significant effects for TLF and FL, respectively. Conclusions The greater tensile strength and stiffness of FL compared to TLF was not reflected in its material properties, implying any difference was a consequence of greater thickness. Suture pullout was not significantly different between the 2 tissues, perhaps limiting the clinical significance of the tissue mechanics. Tissues were anisotropic with respect to mechanical properties, thus orientation may be an important factor.